Do sin tax hikes spur cheating in interpersonal exchange? - Kenchington, David G.; Shohfi, Thomas D.; Smith, Jared D.; White, Roger M. (Accounting, Organizations and Society, 2022)
We study the New York City taxi market to examine whether an excise tax hike on cigarettes corresponds to smoker taxi drivers more frequently cheating their customers. Increased cheating could be motivated by both financial pressures and as a reaction to unfair treatment (as surveyed smokers view cigarette tax hikes as quite unfair). We examine this question using detailed ride-level data where we can identify a rare but fraudulent overcharging technique (cheating) and a subsample of taxi drivers who smoke (affected taxpayers, identified via tickets for smoking in a cab). In difference-in-differences regressions we find that following a cigarette tax hike, taxi drivers who smoke are approximately 1.5 times more likely to cheat customers than other drivers. Our findings are strongest in the subsample of smokers with consistently low earnings.